A Practical Guide for Teaching with Generative AI in Sport Management - Geoffre Sherman; David Pierce (Journal of Applied Sports Management, 2026)
Generative artificial intelligence (GenAI) is reshaping how sport management educators design assignments, evaluate student work, and develop professional competencies. This article presents a practical pedagogical framework that integrates GenAI tools within the Design Council's Double Diamond process—Discover, Define, Develop, and Deliver—to scaffold student thinking across project-based courses. Rather than positioning GenAI as a replacement for student reasoning, the model treats it as a collaborator in roles such as a research assistant, clarifier, creative teammate, and editor. Fluency in prompt engineering is developed progressively through structured exercises that emphasize verification, iteration, and critical evaluation of model outputs. Two complementary assessments—the Prompt and Decisions Portfolio and the Interactive Oral—ensure that authorship, reasoning, and adaptability remain central to evaluation. Aligned with guidance from UNESCO, the U.S. Department of Education, and the NIST AI Risk Management Framework, this approach equips sport management students to engage GenAI ethically, transparently, and with sustained human judgment.
Keywords: AI; ethics; pedagogy; leadership; design thinking